Bridging Iranian Exporters with Foreign Markets : Does Diaspora Matter? - Jamal Ibrahim Haidar; Seyed Hossein Mirjalili (Journal of Economic Integration, 2016)
After matching a rich micro-level Iranian customs dataset with a macro-level cross-country database on Iranian diaspora stocks, we establish that diaspora matters for dynamics of Iranian exporters. We document the extent to which Iranian emigrants foster exports through both intensive and extensive margins at the micro-level. We show that destinations with more emigrants from Iran attract more Iranian exporters and allow them to survive longer and grow faster. One plausible explanation is that the diaspora channel reduces the fixed cost of exporting that Iranian exporters incur to enter a destination, those related to creating distribution channels, and those associated with learning about market demand. Our results add firm-level insight to the burgeoning literature on the channels through which emigration could impact economic integration. As Iran is now trying to integrate more with the global economy, these results suggest that Iranian embassies across the world have a role to play in bridging the gap between Iranian diaspora and exporters through trade promotion exhibitions and workshops to encourage greater trade between Iran and the rest of the world.
Keywords: F10; F20; F22; F23; L14; L25; 330; Economic Integration; Diaspora; Exporters Dynamics; Trade